X-Ray Powder Diffraction of the Complex of S3N3Cl3 with Zn(II) Compound - Rani, Shubha; Singh Jadon, S.P. (Asian Journal of Chemistry, 2016)
On the basis of X-ray powder diffractometric studies, the complex of S3N3Cl3 with ZnO, formulated as (S3N3Cl3)3ZnO is found to be a tridentate co-ordinate complex with distorted tetrahedral geometrical structure.